Effects of non-heating users in heating residential buildings on heat consumption. Issue 1 (1st August 2022) - Gao, X Y; Tang, C L; Meng, X Z; Luo, X L; Yang, X H; Yan, C Q
Abstract: Building heat consumption is affected by factors such as building characteristics, surrounding non-heating users, and outdoor temperature. Therefore, in order to achieve precise and efficient heating, it is of great importance to study the effects of building characteristics and the existence of non-heating users on the building heat consumption. This paper proposed two factors to evaluate the influences of the building characteristics and the non-heating users on heat consumption in a multi-storey heating residential building. Based on the heat consumption without non-heating adjacent users, the top-side users, top-middle users, middle-side users, middle-middle users, bottom-side users and bottom-middle users are identified as six types of typical-location users. Taking the heat consumption of middle-middle users as the benchmark, location factors (LFs) are introduced to consider the influence of building characteristics on the heat consumption of different typical-location users. For each typical-location user, non-heating user factors (NHFs) are introduced to consider the influences of different distributed non-heating adjacent users on the heat consumption of each typical-location user. The results show that, for low-temperature hot water floor radiant heating system, the impact of upstairs adjacent non-heating users is greater than that of same-floor adjacent non-heating users, and the impact of downstairs adjacent non-heating users is minimal. Besides, it can be considered the non-heating user factors vary slightly with the outdoor temperature when the outdoor temperature is below 0 °C. The results provide a guide for heating operation regulation of residential buildings with non-heating users.